Optimizing Religious Tourism As Tourism Attractions For Cultural Resilience (A Case Study Of Religious Tourism In Pangeran Jayakarta Sanctuary) - Mawarni, Ajeng Arum; Puspitasari (Journal of Strategic and Global Studies, 2020)
UNWTO (2020) states that international tourist arrivals is higher 3.8% in 2019 than previous years. UNWTO estimates that tourist destinations around the world will reach 1.5 billion arrivals in 2019 with an increase of around 54 million. This condition has a positive impact especially for the tourism development, but on the other hand social changes as a result of globalization is very vulnerable to occur which give another impact especially the problem of cultural resilience in society. Therefore how to enhance cultural resilience by minimizing the negative influence in tourism development in the globalization era in the Pangeran Jayakarta sanctuary, East Jakarta is important to do. Current tourists’ trend pay more attention to the quality of experience and the tendency to look for something unique and authentic where they cannot found in other places. To fulfill this trend, it can be done by presenting religious tourism as a tourism attraction. Optimizing religious tourism as a tourism attraction in order to enhance the cultural resilience is the aim of this research. The research was conducted by library research and interviews and using descriptive-qualitative analysis. The result shows that the Pangeran Jayakarta sanctuary has the potential of cultural resources that can still be presented in an authentic and contextualized manner. Bringing up the value and meaning of culture and history by making it as a tourism attraction in Pangeran Jayakarta sanctuary is an opportunity for a positive image and local identity with multicultural values, solidarity, unity in diversity, mutual cooperation and pride of local culture.